Influence Rational Emotive Behavior Therapy (REBT) & Acceptance Commitment Therapy (ACT) on Self-Efficacy of HIV Patients - Sugiyanto, Emilia; Chandra Hadi Prasetya; Livana PH; Wijanarko Heru Pramono (Universitas STRADA Indonesia, 2026)
Background: Self-efficacy is a determining factor and predictor of successful treatment for HIV patients. Self-efficacy contributes to a person's ability to overcome the challenges they face. Efforts to manage self-efficacy in HIV patients are needed to support treatment success. One approach is to use a combination of Acceptance Commitment Therapy (ACT) and Rational Emotive Behavior Therapy (REBT). Purpose: The aim of this study was to determine the effect of providing combination therapy of ACT and REBT on increasing self-efficacy in HIV patients. Methods: This study used a quantitative, semi-experimental, one-group pre-test and post-test method. The study population consisted of 31 respondents. The sampling method was total sampling. The study was conducted on 31 HIV patients with at least adequate self-efficacy scores. The Wilcoxon test was used for analysis because the data used were ordinal. Results: There was an effect of combined ACT and REBT therapy on improving self-efficacy in HIV patients, as indicated by a significant value of 0.00. Respondents experienced an increase in efficacy values before and after with an average increase of 16 with a sig value of 0.00 where the value is less than 0.05, which means there is a difference in value between the efficacy values before and after. There is an effect of administering ACT and REBT therapy on the efficacy level of HIV patients. Conclusion: ACT and REBT therapy have been shown to improve self-efficacy in HIV patients. Self-efficacy in HIV patients is influenced by several factors, including patient demographics and stigma. The development and implementation of therapy, particularly for vulnerable groups, is needed, taking into account each patient's characteristics.